Biological activities, isolated compounds and HPLC profile of Verbascum nubicum - Heba Abd El Hady El Gizawy; Mohammed Abdalla Hussein; Essam Abdel-Sattar (Taylor & Francis Group, 2019)
Context: Genus Verbascum (Scrophulariaceae) comprises about 360 species of flowering plants. Verbascum has been used in traditional medicine as an astringent, antitussive, analgesic and anti-inflammatory. Objective: Nothing was found in the available literature concerning Verbascum nubicum Murb; therefore, the study evaluates the biological activities, isolated compounds and HPLC profile. Materials and methods: Methanol extract (VME) and butanol fraction (VBF) of air-dried powdered V. nubicum were obtained. Four compounds were isolated from VBE and identified by 1H- and 13C-NMR. High-performance liquid chromatography (HPLC) profile was determined for (VME). LD50, in vitro antioxidant, in vivo antiulcerogenic and anti-inflammatory activities as well as hepatoprotective activity were assessed. Anti-ulcerogenic and hepatoprotective activities were supported by histopathological examinations. Results: HPLC analysis of VME revealed the presence of luteolin 7-glucoside (2215.43 mg/100 g), hesperidin (954.51 mg/100 g) and apigenin (233.15 mg/100 g) as major compounds. Four compounds were isolated and confirmed by NMR data, were identified as gentiopicroside, luteolin, aucubin and gallic acid. The LD50 of VME and VBF extracts were calculated to be 8200 and 4225 mg/kg b.w., respectively. IC50 values of VBE and VMF as measured by DPPH·method were 43.6 and 50 µg/mL, respectively. Also, anti-inflammatory effect of VME (400 mg/kg b.w.) and VBF (200 mg/kg b.w.) induced edema model after 120 min were 61.93 and 56.13%, respectively. Antiulcerogenic activity of VME (400 mg/kg b.w.) and VBF (200 mg/kg b.w.) in albino rats were 65.14 and 84.57%, respectively. Conclusions: The V. nubicum extracts displayed safe and promising antioxidant, anti-inflammatory and hepatoprotective properties. It can be also applied in the pharmacy industry, food industry and healthcare.